Geochemical Investigations of Minerals in the Antarctic - Watanuki, Kunihiko; Torii, Tetsuya; Nishiyama, Takashi; Morikawa, Hideki (1979)
P(論文) Many evaporites, such as halite, sylvite, epsomite, mirabilite, bloedite, gypsum, carphosiderite, aragonite, hexahydrite and atakamite were found around Syowa Station. These minerals are thought to have been formed by sea spray and/or concentration under the frigid condition, and in some cases by rock weathering. Garnet and euxenite were analyzed from the view points of geochemistry and mineralogy. On the other hand, a new mineral, antarcticite, was found by geochemical investigation in the Dry Valleys. In the Dry Valley Drilling Project, many evaporites and secondary minerals were analyzed by X-ray and chemical method, and from these results the geological processes in the Dry Valley were clarified to some extent. departmental bulletin paper